Neuroleukin: A potential cerebrospinal fluid biomarker for Alzheimer's disease: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - de Kort, Anna M.; Kuiperij, H. Bea; Kersten, Iris; Versleijen, Alexandra A.M.; Schreuder, Floris H.B.M.; Klijn, Catharina J.M.; Claassen, Jurgen A.H.R.; Verbeek, Marcel M.
Abstract: Background: Neuro‐inflammation is an important mechanism that occurs during the early stages of AD, and this can be studied indirectly via the CSF. Neuroleukin (NLK) can serve as an interesting new inflammatory marker. NLK is a lymphokine product of lectin‐stimulated T‐cells and induces immunoglobulin secretion by human mononuclear cells. 1 Moreover, it can serve as a neurotrophic factor for spinal and sensory neurons. Furthermore, It has previously been shown that neuroleukin is expressed in neurons, microglia, oligodendroglia, and in cerebrovascular cells such as smooth muscle cells. In addition, expression of neuroleukin was found in senile plaques and in Aβ‐laden vessels. 2 Thus, the aim of our study was to investigate the diagnostic and discriminative value of NLK cerebrospinal fluid (CSF) in patients at various clinical stages of Alzheimer's disease (AD) and in patients with cerebral amyloid angiopathy (CAA). Method: CSF NLK were quantified by ELISA. Cohorts of controls (n=47), patients with AD (n=59; consisting of 19 patients with mild cognitive impairment (clinical dementia rating (CDR) = 0.5), 28 patients with CDR 1.0 and 12 patients with a CDR of ≥ 2.0.) and patients with CAA (n=28) were used to evaluate the diagnostic value of CSF NLK levels. Result: We found that NLK levels were significantly elevated in the CSF of AD patients (4.64 ng/ml (IQR: 3.69‐5.57) compared to controls (3.29 ng/ml (IQR: 2.39‐3.94); p<0.0001) and levels were also significantly elevated in patients with mild cognitive impairment. In CAA patients, NLK was not elevated (3.39 ng/ml, IQR 2.94‐4.17). NLK correlated with total tau levels (rSP = 0.653, p < 0.0001), phosphorylated tau levels (rSP = 0.604 p < 0.0001) and to a lesser extent with amyloid β42 levels (rSP = ‐0.294, p < 0.0001). Conclusion: Our findings indicate that CSF NLK levels are elevated in AD patients compared to controls and support an increased neuroinflammatory state in the various stages of AD. In addition, NLK appears to be associated with neurodegeneration as measured by total tau and phosphorylated tau. References: 1. Chaput et al. Nature, 1988. 332(6163): p. 454‐455, 2. Rensink et al. Neuropathology and Applied Neurobiology, 2004. 30(3): p. 279.